When the Part Mirrors the Whole: Interactions Beyond “Simple Location” - Gomez-Marin, Alex; Arnau, Juan (Frontiers in Psychology, 2021)
Reductionism relies on expectations that it is possible to make sense of the whole by studying its parts, whereas emergentism considers that program to be unattainable, partly due to the existence of emergent properties. The emergentist holistic stance is particularly relevant in biology and cognitive neuroscience, where interactions amongst system components and environment are key. Here we consider Alfred North Whitehead's philosophy as providing important insights to metaphysics of science in general, and to the reductionism versus emergentism debate in particular. An appraisal of Whitehead’s perspective reveals a difficulty shared by both approaches, referred by him as “simple location”: the commitment to the idea that the nature of things is exhausted by their intrinsic or internal properties, and does not take into account relations or dynamic interactions denoting “togetherness”. In a word, that things are simply where they are. Whitehead criticizes this externalist ontological perspective in which each interacting element exists, and can be thought, without essential reference to other elements. The aim of this work is to uncover such a stance, particularly in the context of dynamical systems, and to show its shortcomings. We propose an alternative relational approach based on Whitehead’s notion of “internal relations”, which we explicate and illustrate with several examples. Our work aims to criticize the notion of simple location, even in the framework of emergentist accounts, so as to contribute to a “relational turn” that will conceive “inter-identities” as "intra-identities" in which interactants are not enduring substances, but internally related processes. In sum, we argue that the notion of internal relations has a strong theoretical power to overcome some fundamental difficulties in the study of life and mind.